2020
DOI: 10.1021/jacs.0c05675
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenative Depolymerization of Nylons

Abstract: The widespread crisis of plastic pollution demands discovery of new and sustainable approaches to degrade robust plastics such as nylons. Using a green and sustainable approach based on hydrogenation, in the presence of a ruthenium pincer catalyst at 150 °C and 70 bar H 2 , we report here the first example of hydrogenative depolymerization of conventional, widely used nylons and polyamides, in general. Under the same catalytic conditions, we also demonstrate the hydrogenation of a polyur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 63 publications
2
130
0
Order By: Relevance
“…Interestingly, lowering the base loading to 2 mol% while keeping the remaining conditions the same, resulted in a lower yield of methanol and aniline (entry 12). This is suggestive of a dual role of base: (a) to generate the coordinatively unsaturated ruthenium complex (catalytically active species) by the N−H deprotonation and concomitant abstraction of chloride ligand from the precatalyst 5 , and (b) to assist in the hydrogenation process by enabling facile decomposition of a hemiaminal intermediate as suggested earlier for the hydrogenation of amides [22] …”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, lowering the base loading to 2 mol% while keeping the remaining conditions the same, resulted in a lower yield of methanol and aniline (entry 12). This is suggestive of a dual role of base: (a) to generate the coordinatively unsaturated ruthenium complex (catalytically active species) by the N−H deprotonation and concomitant abstraction of chloride ligand from the precatalyst 5 , and (b) to assist in the hydrogenation process by enabling facile decomposition of a hemiaminal intermediate as suggested earlier for the hydrogenation of amides [22] …”
Section: Methodssupporting
confidence: 52%
“…Addition of the first equivalent of H 2 to a urea derivative results in the formation of a formamide intermediate with the concomitant release of an amine molecule. Further hydrogenation of the formamide intermediate results in the formation of a hemiaminal intermediate that could undergo transition‐metal or base‐assisted C−N cleavage [22] to form another equivalent of amine and formaldehyde. Subsequent hydrogenation of formaldehyde produces methanol.…”
Section: Methodsmentioning
confidence: 99%
“…34 In order to establish a circular economy, the development of new recycling methods is of particular interest. Most recently, Milstein et al and Schaub et al demonstrated that the hydrogenation of polyurethane is possible, 79,80 and valuable chemical such as diols, diamines and methanol can be obtained. Thus, we extended this new strategy to the transfer hydrogenation of polyurethanes (Figure 5).…”
Section: Recycling Of Polyurethanes To Valuable Productsmentioning
confidence: 99%
“…In an earlier paper, the hydrolysis of nylon-6 was achieved by a combination of zinc chloride (40 wt %) and phosphoric acid (20 wt %) under microwave irradiation, however, resulting in a mixture of linear and cyclic oligomers at 89% polymer conversion [ 121 , 331 ]. While drafting the present review, the first example of catalytic hydrogenative depolymerisation of polyamides and polyurethanes was described, using soluble Milstein-type Ru–pincer complexes (2 mol %), DMSO solvent and K t- BuO cocatalyst at 150 °C and 70 bar H 2 [ 332 ]. Typically, a selectivity to the corresponding diols/diamines/amino alcohols in the range of 20–80% was observed at 60–99% conversion, depending on the polymeric substrate.…”
Section: Reviewmentioning
confidence: 99%